Identifikasi Potensi Ekowisata Mangrove dan Konservasi Alam di Desa Binuanga Kabupaten Bolaang Mongondow Utara - Lahay, Rakhmat Jaya; Kumaji, Syam S.; Yusuf, Daud; Mohamad, Nurdin; Zainuri, Ahmad; SM, Farid (Universitas Negeri Gorontalo, 2024)
The potential for ecotourism development in the mangrove area in Binuanga Village needs to be explored in order to present environmentally based information. This article is part of community service activities by the Gorontalo State University postgraduate program. Community service activities aim to collect data related to ecotourism and conservation potential for the development of mangrove tourism. Data collection uses a dialogue, discussion and interview approach with the government and local communities. The output of this service activity are the types of mangrove species found at the service location and changes in the region of the mangrove area over the last 4 years. In the future, service activities will be further enhanced in depth to obtain complete data on the sustainable development of ecotourism and mangrove conservation in Binuanga Village.